MANAGEMENT OF RADIOTHERAPY IN CLINICAL CA MAMMAE AT THE RADIOTHERAPHY INSTALLATION OF ARIFIN ACHMAD HOSPITAL PEKAN BARU - Nuzul Rahmawati Fitria; Muhammad Habib Irfan (LPPM Universitas Awal Bros, 2024)
Background: Breast cancer (Ca mammae) is one of the malignancies requiring multimodal management, one component of which is radiotherapy. The success of radiotherapy is determined not only by radiation dose delivery but also by the accuracy of simulation, target delineation, treatment planning, positioning verification, and radiation delivery. This study aimed to determine the management of radiotherapy in patients with clinical Ca mammae at the Radiotherapy Installation of Arifin Achmad Regional General Hospital, Pekanbaru. Methods: This study employed a qualitative descriptive method with a case study approach. Data were collected in June 2024 through participatory observation, interviews with radiotherapy staff and medical physicists, and documentation. The study sample consisted of one female patient diagnosed with right-sided Ca mammae at stage T4bN1M0, triple-negative, post six cycles of neoadjuvant chemotherapy, with a partial response, and post-radical mastectomy with lymph node dissection. Results: Radiotherapy management included consultation at the radiation oncology clinic, simulation using a CT simulator with a breast board and knee support, target delineation through contouring, treatment planning using a Treatment Planning System (TPS), geometric and portal verification, and radiation delivery using a LINAC. The patient received one treatment phase with a dose of 25 × 2 Gy. Conclusion: Radiotherapy management for Ca mammae at Arifin Achmad Regional General Hospital, Pekanbaru, was performed in a sequential and integrated manner, from simulation to radiation delivery. The use of a CT simulator, TPS, immobilization devices, geometric verification, and LINAC contributed to accurate radiation delivery while supporting the protection of healthy tissues.